(untitled) (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2025)
The different characteristics of men and women affect the selection of different language characters between men and women. However, the rise of non-binary gender challenges the rigid categorization of language as masculine or feminine. This study aimed to identify the language features used by Sam Smith as a non-binary individual and the influence of social factors in their selection. The data were collected using a documentation method in the form of utterances uttered by Sam Smith in two YouTube interviews. A descriptive qualitative method is used to analyze the data using the theory of language features by Coates (2013) and the theory of social factors that influence language use by Holmes (2013). The findings show that Sam Smith used all seven types of language features in the interview with a male interviewer. Meanwhile, with a female interviewer, only six types of language features were used, where the commands and directives features were not found. This study further revealed that there were differences in the frequency of language features used in the two interviews, which were influenced by social factors, including participants, setting, topic, and function.